FiltroVis: An OpenCV user interface in Flet - Chávez Bosquez, Oscar (2026)
This article describes the development of FiltroVis, an interactive, cross-platform user interface (UI) for the real-time application and visualization of classic computer vision filters. We employed an incremental methodology, structured into three successive prototypes, using the Flet framework to build the graphical interface and the OpenCV library for video processing. Performance issues were addressed by implementing concurrent processes. Satisfactory results were obtained in terms of functionality and real-time performance, achieving the correct application of each filter and demonstrating the system’s portability across operating environments such as Windows, Linux, and macOS, as well as via the web. The goal of FiltroVis is to offer a free, functional educational tool that integrates theoretical foundations with accessible tools such as Flet and OpenCV.